Origin of Bedding-Parallel Calcite Veins from Lacustrine Shale in the Eocene Dongying Depression, Bohai Bay Basin, China. (21st December 2020) - Shen, Zhenhuan; Yu, Bingsong; Bai, Chenyang; Han, Shujun; Liu, Huimin
Abstract : Calcite veins, which developed parallel to the bedding, are widespread in laminated source rocks in the Eocene Dongying Depression. However, there is a lack of systematic description and classification of the veins. This study presents a systematic characterization of the calcite veins, host rocks, and micritic carbonate laminae by applying petrographic and geochemical methods to understand vein-forming mechanisms. Antitaxial and syntaxial veins are examined. Antitaxial veins contain typical fibrous crystals with the most intense fluorescence, and the median zone of these veins is often the micritic carbonate. Calcite crystals in syntaxial veins develop a blocky morphology of various sizes, indicating obvious growth competition. Data of rare earth elements and trace elements obtained from the micritic laminae, host rocks, and calcite veins are very similar. This indicates that the vein-forming nutrients originated from the carbonate in the host rocks and micritic laminae. The minor difference in C and Sr isotopes between calcite veins and micritic carbonate within the host rock and the negative shift in O isotopes in the veins are caused by ion exchange and dehydration of swelling clay minerals in the burial environment. This further proves that the calcite veins are formed in a closed system. Geochemical analysis suggests that the rocks are in the oil window and have good hydrocarbon potential. Thermal evolution of the acidic fluids generated from organic matter (OM) resulted in the dissolution of carbonate and formed fluid overpressure in the rocks. Fluid overpressure induced the formation of fractures in the interlayer and expanded the veins with the force of crystallization due to fibrous calcite growth. Blocky crystals grow in the fractures from the margins toward the center. Hydrocarbon expulsed via OM maturation in the host rock fills the intercrystalline pores. Moreover, shale with bedding-parallel calcite has the characteristics of high-quality shale oil reservoirs. These characteristics will probably provide guidance for shale oil exploration.